(untitled) (International Journal of Engineering and Computer Science, 2015)
—the availability bandwidth in MANET is fixed, that is creating the problem of bottleneck and the load in network is increased. In MANET if the congestion is occur then the performance of network is gradually decreased according to time. In this research we proposed the new congestion control load balancing technique with varying the buffer size of queue in dynamic network with reliable multipath AOMDV protocol. The multipath routing protocol AOMDV is also balance the load by providing alternative path but not capable at all situation. The AOMDV is provides the multiple path for data sending, if the one is fail and the varying queue length is handled the data packets that cross the decided queue maximum. The queue is incremented and the storing and forwarding capability of nodes is also improved. The proposed load balancing proposal is proficiently handled the load on the network. If the node being a component of communication is moves out of range then the AOMDV is reduced the overhead and re-establishment of connection in between sender and receiver. The proposed method is increase the routing capability of AOMDV protocol. The achievement of AOMDV and proposed varying queue is evaluated through performance metrics and observe the performance of proposed scheme is better.